Thiadiazole Cyclic Derivatives from Aldamine Compounds (Preparation, Characterization, Thermal Stability) - Athraa Sahib Alrammahi (Journal of Global Pharma Technology, 2018)
Seven  heterocyclic  derivatives  were  synthesized  by   using  Azotation  reaction  ,followed  by  coupling  reaction  with  phenol  derivative  , the  resulting   compound  cyclized   with  thiosemicarbazide   to  yield  thiadiazole  derivatives  which  reacted  with  carbonyl  compound ( benzaldehyde) with  drops  of  glacial   acetic  acid  to  produce  imine  compound   followed  by  breaking  of  imine  bond (CH=N) to  react   with  ( succinic  anhydride , chloroaceto chloride  , glycine , ortho mercapto benzoic  acid )  to  yield  cyclic  derivatives  from  Aldamine-thiadiazole  derivatives.  Thiadizole-aldamine  derivatives   were  characterized   by  chemical   techniques  such as (1H NMR , IR  and  Mass-  spectra ,  Thermal  Stability).Keywords: Therm, Technic, Stable.